EKSISTENSI TOKOH PEREMPUAN DALAM NOVEL NYONYA JETSET KARYA ALBERTHIENE ENDAH - SETYA KEMALA SARI, NIKMAS (BAPALA, 2018)
The phenomenon of life that occurs in society in general in the form of social problems. One of the social problems that occurs in society is gender bias with all the stigma that discredits women and puts men at the center of life. This happens because people do not understand well the gender roles that exist in the community, so that the negative stigma of women continue to occur for generations that ultimately form the construction of patriarchal society. This research includes the type of qualitative research because this research data in the form of words and description of sentences according to research problems. The approach used in this research is mimetic approach. There are two types of data sources in this study, namely primary and secondary date sources. The primary date source in this research is Alberthiene Endah Nyonya Jetset novel while secondary data source of this research is factual news related to research problem. Date collection techniques used in this study is a library technique. library techniques is a technique of date collection using literature sources as reference research applied when searching and collecting data from text books, encyclopedia, monograp, and the like. The result of this research is literature is a reflection of a phenomenon of life in society. however, in literature does not necessarily tell the details of life in society, it only has the same story and storyline. Kaywords : Literature work, Feminist, Existence, Nyonya Jetset.